2018
DOI: 10.1177/0969733018761171
|View full text |Cite
|
Sign up to set email alerts
|

Professional self-concept and professional values of senior students of the nursing department

Abstract: In order to improve students' perceptions of professional self-concept and professional values, it is thought that students' awareness should be increased on these topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 20 publications
(24 reference statements)
2
34
0
3
Order By: Relevance
“…If we consider our results together with other international studies (Alkaya et al ; Ayla et al ; Çöplü & Tekinsoy Kartın), most studies have found that overall, nursing students demonstrate a high regard for professional values. However, some authors (Alkaya et al ) have detected differences between nursing students in America and Turkey, suggesting a different view of nursing and the influence of other possible factors, such as nurses' access to better living conditions when choosing this profession.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…If we consider our results together with other international studies (Alkaya et al ; Ayla et al ; Çöplü & Tekinsoy Kartın), most studies have found that overall, nursing students demonstrate a high regard for professional values. However, some authors (Alkaya et al ) have detected differences between nursing students in America and Turkey, suggesting a different view of nursing and the influence of other possible factors, such as nurses' access to better living conditions when choosing this profession.…”
Section: Discussionsupporting
confidence: 69%
“…Concerning this issue, according to various studies conducted in Turkey (Çöplü & Tekinsoy Kartın) or Iran (Badiyepeyma et al ) in general, a more internalized experience of the concept of nursing has been confirmed among the female students in relation to the professional attributes, professional self‐concept or willingness to remain in the profession. Furthermore, as other authors have commented (Bijani et al ), there is an important gender influence in professional values, especially in female students.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some studies also explored how nurses' self-concept and professional identity and the in uence on image of nursing [14,15].The issue of nursing image is dynamic and ought to be understood from different context. In recent times, midwives have tried to also create an identity beyond being known as nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Several determinants may influence nurses’ personal and professional self-concept, including work environment, personal and professional values, education and culture, as well as interaction with colleagues, other healthcare professionals and patients ( Ewens, 2003 ; Kantek and Şimşek, 2017 ; Çöplü and Tekinsoy Kartın, 2018 ). Other data show that nurses partially form some characteristics of their professional self-concept from their public image ( Emeghebo, 2012 ; ten Hoeve et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%